LEXICOGRAPHIC ANALYSIS OF THE POLYSEMY OF LEXEMES DEFINING THE CONCEPT OF "COLOR" IN THE ENGLISH LANGUAGE - Utepbergenova, D. (ILIM hám JÁMIYET, 2025)
This article focuses on the lexicographic analysis of the polysemy of lexemes representing the concept of "color" in the English language. The research aims to examine how color-denoting words acquire different meanings depending on the context and to identify the key factors contributing to their polysemy. The study is based on data from major English dictionaries and corpus-based text analysis, allowing for the identification of the main trends in the semantic development of color lexemes. Special attention is given to metaphorical and culturally specific meanings that emerge as a result of semantic expansion.